Correlation Analysis of Ergonomic Position with the Incident of Low Back Pain in Batik Craftsmen in Proppo District, Pamekasan Regency - Kurniadi, Bangbang; Budiono, Nugrahadi Dwi Pasca (PROMOTOR, 2024)
Low back pain can occur due to unergonomic positions, especially when batik craftsmen use the wrong position and sitting posture while making batik. This study aims to analyze the correlation between ergonomic positions and low back pain among hand-written batik craftsmen in the Proppo District, Pamekasan Regency. Method: Correlation analysis with a cross-sectional approach. The population is all written batik craftsmen in Proppo District, Pamekasan Regency, totaling 85 batik craftsmen. The sample size was 70 hand-written batik craftsmen who were determined using simple random sampling. The independent variable is the ergonomic position, while the dependent variable is the incidence of low back pain. The instruments used were an ergonomic position questionnaire and The Oswestry Disability Index (ODY) to observe low back pain. The statistical analysis used is the Contingency Coefficient with α = 0.05. Results: statistical tests show the p-value: 0.014 < α: 0.05 with a correlation coefficient value of 0.281 so H1 is accepted. This means that there is a significant relationship between ergonomic position and low back pain with a medium level of tightness that is positive. Conclusion: The worker's static posture is carried out in a sitting position, long duration of time and repetitive movements when making batik have an impact on changes in body posture which increases the risk of low back pain